Evacuation proctography: a reappraisal of normal variability. (July 2014) - Palit, S.; Bhan, C.; Lunniss, P. J.; Boyle, D. J.; Gladman, M. A.; Knowles, C. H.; Scott, S. M.
Abstract Aim Interpretation of evacuation proctography (EP) images is reliant on robust normative data. Previous studies of EP in asymptomatic subjects have been methodologically limited. The aim of this study was to provide parameters of normality for both genders using EP. Method Evacuation proctography was prospectively performed on 46 healthy volunteers (28 women). Proctograms were independently analysed by two reviewers. All established and some new variables of defaecatory structure and function were assessed objectively: anorectal dimensions; anorectal angle changes; evacuation time; percentage contrast evacuated; and incidence of rectal wall morphological 'abnormalities'. Results Normal ranges were calculated for all main variables. Mean end‐evacuation time was 88 s (95% CI: 63–113) in male subjects and 128 s (95% CI: 98–158) in female subjects; percentage contrast evacuated was 71% (95% CI: 63–80) in male subjects and 65% (95% CI: 58–72) in female subjects. Twenty‐six (93%) of 28 female subjects had a rectocoele with a mean depth of 2.5 cm (upper limit = 3.9 cm). Recto–rectal intussusception was found in nine subjects (approximately 20% of both genders); however, recto–anal intussusception was not observed. Only rectal diameter differed significantly between genders. Qualitatively, three patterns of evacuation were present. Conclusion This study defines normal ranges for anorectal dimensions and parameters of emptying, as well as the incidence and characteristics of rectal‐wall 'abnormalities' observed or derived from EP. These ranges can be applied clinically for subsequent disease comparison.